Angiographic Outcome of Endovascular Stroke Therapy Correlated with MR Findings, Infarct Growth, and Clinical Outcome in the DEFUSE 2 Trial. Issue 7 (October 2014) - Marks, Michael P.; Lansberg, Maarten G.; Mlynash, Michael; Kemp, Stephanie; McTaggart, Ryan A.; Zaharchuk, Greg; Bammer, Roland; Albers, Gregory W.; ,
Background: DEFUSE 2 demonstrated that patients with magnetic resonance imaging mismatch had a favorable clinical response to tissue reperfusion assessed by magnetic resonance imaging. This study reports the endovascular results and correlates angiographic reperfusion with clinical and imaging outcomes. Methods: Prospectively enrolled ischemic stroke patients underwent baseline magnetic resonance imaging and started endovascular therapy within 12 h of onset. Patients were classified as either target mismatch or no target mismatch using magnetic resonance imaging. The pre- and postprocedure angiogram was evaluated to determine thrombolysis in cerebral infarction scores. Favorable clinical response was determined at day 30, and good functional outcome was defined as a modified Rankin Scale 0–2 at day 90. Results: One-hundred patients had attempted endovascular treatment. At procedure end, 23% were thrombolysis in cerebral infarction 0–1, 31% thrombolysis in cerebral infarction 2A, 28% thrombolysis in cerebral infarction 2B, and 18% thrombolysis in cerebral infarction 3. More favorable thrombolysis in cerebral infarction-reperfusion scores were associated with greater magnetic resonance imaging reperfusion ( P < 0·001). thrombolysis in cerebral infarction scores correlated with 30-day favorable clinical response ( P = 0·041) and 90-day modified Rankin Scale 0–2 ( P = 0·008). These correlations were significant for target mismatch patients at 30 days ( P = 0·034) and 90 days ( P = 0·003). Infarct growth was strongly associated with poorer thrombolysis in cerebral infarction scores in target mismatch patients ( P < 0·001). Patients with thrombolysis in cerebral infarctionnfarction 2A reperfusion had less magnetic resonance imaging reperfusion ( P = 0·004) and poorer clinical outcome at 90 days ( P = 0·01) compared with thrombolysis in cerebral infarction 2B-3 patients. Conclusion: Thrombolysis in cerebral infarction reperfusion following endovascular therapy for ischemic stroke is highly correlated with magnetic resonance imaging reperfusion, infarct growth, and clinical outcome.